Leiomyoma at an Unusual Site: A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Uterine leiomyomas are one of the most common tumors found in women of reproductive age. Leiomyoma is usually derived from uterine smooth muscle but sometimes it may arise from an unusual site, have rarely been reported in this age group.In this present case, vaginal fibroid caused clinical dilema. Here, we report the rare case of a leiomyoma in a 27-years married, nuliparous lady; presented with dyspareunea and rectal pain treated by myomectomy. The treatment of the symptomatic fibroid is either myomectomy or hysterectomy1. A liomyoma was located in rectovaginal septum and , at the junction middle and lower one third of vagina and above the anal canal, separate from the uterus. Histopathological examination confirmed as a case of leiomyoma.Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 44-46